Dual Role of Hepatic Macrophages in the Establishment of the Echinococcus multilocularis Metacestode in Mice - Wang, Hui; Zhang, Chuan-Shan; Fang, Bin-Bin; Hou, Jiao; Li, Wen-Ding; Li, Zhi-De; Li, Liang; Bi, Xiao-Juan; Li, Liang; Abulizi, Abuduaini; Shao, Ying-Mei; Lin, Ren-Yong; et al. (Frontiers in Immunology, 2021)
Echinococcus multilocularis larvae, predominantly located in the liver, cause a tumor-like parasitic disease, alveolar echinococcosis (AE), that is characterized by increased infiltration of various immune cells, including macrophages, around the lesion that produces an “immunosuppressive” microenvironment, favoring its persistent infection. However, the role of hepatic macrophages in the host defense against E. multilocularis infection remains poorly defined. Using human liver tissues from patients with AE and a hepatic experimental mouse model of E. multilocularis, we investigated the phenotype and function of hepatic macrophages during parasite infection. In the present study, we found that a large number of CD68+ macrophages accumulated around the metacestode lesion in the liver of human AE samples and that both S100A9+ proinflammatory (M1 phenotype) and CD163+ anti-inflammatory (M2 phenotype) macrophages were significantly higher in close liver tissue (CLT) than in distant liver tissue (DLT), whereas M2 macrophages represent the dominant macrophage population. Furthermore, E. multilocularis-infected mice exhibited a massive increase in macrophage (F4/80+) infiltration in the liver as early as day 5, and the infiltrated macrophages were mainly monocyte-derived macrophages (CD11bhi F4/80int MoMFs) that preferentially differentiated into the M1 phenotype (iNOS+) at the early stage of E. multilocularis infection and then polarized to anti-inflammatory macrophages of the M2 phenotype (CD206+) at the chronic stage of infection. We further showed that elimination of macrophages by treatment of mice with clodronate-liposomes before E. multilocularis infection impaired worm expulsion and was accompanied by a reduction in liver fibrosis, yielding a high parasite burden. These results suggest that hepatic macrophages may play a dual role in the establishment and development of E. multilocularis metacestodes in which early larvae clearance is promoted by M1 macrophages while persistent metacestode infection is favored by M2 macrophages.